Signature of Our Race: Herbert Read and the Line that Links Medieval Illumination and 1930s British Modernism. (2nd April 2016) - Aspinall, Kate
Abstract : In an article in The Burlington Magazine of 1933, British theorist Herbert Read (1893–1968) proposed "a basic linear signature of our race." His invocation of line as a mark of identity is representative of a wider community of thinkers who linked the British avant-garde with medieval illumination via the watercolors of the late eighteenth and early nineteenth centuries. Theorists and scholars such as Kenneth Clark (1903–1983), William George Constable (1887–1976), and Nikolaus Pevsner (1902–1983) joined Read in identifying drawing as an essential aspect of medieval illumination that had re-emerged in the compositions of the Romantic period as well as those of the Neo-Romantics, including John Piper (1903–1992) and Paul Nash (1889–1946). Theoretical enthusiasm for this lineage arose not only from aesthetic affinities but also from political utility. Amid concerns over mounting political extremism, notions of medieval art were useful as emblems of British precedent for sustainable and proud work. This paper traces the use of line at the time, most notably by Read, as a symbolic mark that promoted a balance between individualism and collectivism through its connection to the medieval period. Furthermore, I argue that harnessing the moral connotations of line was possible, and particularly effective, because of culturally available understandings of the drawn line's distinctive intimacy.